Effect Peppermint Aromatherapy Inhalation Reducing Nausea And Vomiting In First Trimester Of Pregnancy - Elsa Yuliani, Putu; Suindri, Ni Nyoman; Wirata, I Nyoman (Poltekkes Kemenkes Semarang, 2023)
The Nausea and vomiting in pregnant women in the first trimester was physiologically due to an increase in the Human Chorionic Gonadotrophin (HCG) hormone which affects the digestive system, causing complaints of nausea and vomiting. One of them was handling nausea and vomiting by administering peppermint aromatherapy inhalation. Peppermint had a sharp menthol aroma, a distinctive cold refreshing smell, and the smell of menthol which had properties against contractions by inhibiting muscle contact caused by serotonin hormone so that it could successfully overcome nausea and vomiting in pregnant women. This study aims to determine the differences in nausea and vomiting before and after administration of peppermint aromatherapy inhalation dose, 0,1-0,2 ml for 1-10 minutes to pregnant women in their first This type of research was quasi-experimental, one-group pre-and post-test design. The number of samples was 48 respondents intervention and treatments, with the sampling method